1-Benzyl-5-methylindoline-2,3-dione - N. Sharmila; T. V. Sundar; G. Satish; P. Venkatesan (IUCrData, 2016)
The title compound, C16H13NO2, is an isatin (indole-2,3-dione) derivative. The isatin moiety is almost planar with an r.m.s. deviation of 0.022 Å, and its mean plane makes a dihedral angle of 74.19 (12)° with the benzyl ring. In the crystal, molecules are linked by C—H...O hydrogen bonds, forming C(6) chains propagating along the a-axis direction. The chains are linked via C—H...π interactions, forming slabs parallel to the ab plane. Within the slabs there are weak π–π interactions present involving inversion-related isatin moieties.